Influence of Female Leadership Styles and Organization Culture on Locus of Control and Job Satisfaction - Muh Akil Rahman (Integrated Journal of Business and Economics (IJBE), 2018)
This study is categorized in exploratory research and included in the descriptive analysis. The population of this research is all lecturers in UIN Alauddin Makassar, Indonesia. The sampling technique used in this research is purposive sampling which sample criterion used is civil servant lecturers who occupy structural positions. The sample size uses maximum likelihood (ML) with 105 numbers of samples. In this study, the techniques used include questionnaire; observation; interviews, and documentation. The method of analysis used in this research is structural equation modelling (SEM) analysis. Findings of this research are female leadership style influence on the locus of control and job satisfaction; organizational culture influences the locus of control and job satisfaction, meanwhile locus of control influence on job satisfaction.